Speech by President of the Society of Neuro-Psychiatry and Legal Medicine - Valega, Juan Francisco (1952)
I must, first, thank the Lord really Rector of the National University of San Marcos, Dr. Pedro Dulanto, for agreeing shaped by significant others to a request for us to make it on behalf of the Society of Neuro-Psychiatry and Legal Medicine in his high chair the solemn opening of the Peruvian Centennial Commemoration of the Birth of Santiago Ramón y Cajal.